ON SOME ASPECTS OF GROUND WATER SIMULATION AND REPRESENTATION OF CONCEPTUAL HYDROGEOLOGICAL MODEL OF SHIRAK BASIN (Proceedings of the YSU C: Geological and Geographical Sciences, 2007)
Modern approaches of ground water simulation, and also the description of constructed by authors of 3-D conceptual model of Shirak basin have been discussed in the article. The topographical map of investigated area in scale 1:100000, geological map in the same scale, and also the description of boreholes, drilled in the last 60 years. On constructed longitudinal and lateral cross-sections of the investigated area and by various interpolation methods the conceptual hydrostratigraphic model has been constructed. The feature of the model is flexibility to updating in the process of reception of new authentic actual materials of investigated area.
Keywords: ground water; Shirak basin; 3-D conceptual model